Influence of human resources development on technical college teachers’ self-concept and productivity in Ogun State, Nigeria - Aderinto, Idowu Dare; Mukaila, Abiodun Yisa; Fadairo, Olatunji Oriola (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2024)
The productivity of any establishment is heavily relied on the welfare of its workers which is a determinant to degree of their output. Hence this study examined the influence of human resources development on technical college teachers’ self-concept, and productivity in Ogun State. Descriptive survey research design was adopted for the study. The population for this study comprised all technical college teachers in Ogun State with sample size of 60 technical college teachers. Structured questionnaire was data collection. Cronbach Alpha reliability technique was used to establish the internal consistency of the instrument and a reliability coefficient of 0.85 was obtained. Data was analyzed with descriptive statistics of mean and standard deviation for answering research questions, while the hypothesis was tested using Correlation Matrix and linear regression. The findings revealed that there is significant influence of human resources development on technical college teachers’ self-concept (β =.748; p ˂ 0.05) and their productivity (β = .830; p ˂ 0.05). It was concluded that human resources development must be embraced to regularly update educators’ skills. Recommendation include that relevant human resources management programmes such as workshops, conferences, short-term programs among others should be introduced to improve self-concept and productivity of technical college teachers.